Julius Caesar - Stewart, Diana; Shaw, Charles, 1941-2005; Shakespeare, William, 1564-1616. (Milwaukee : Raintree Publishers, 1981)
Brutus, best friend of the Roman ruler Caesar, reluctantly joins a successful plot to murder Caesar and subsequently destroys himself.
Keywords: Caesar, Julius -- Juvenile drama; Caesar, Julius -- Drama; Plays